فاعلية العلاج المعرفي المستند الى الوعي الكامل - رافات, أحمد (جامعة الوادي - University of Eloued, 2019)
توجهت هذه الدراسة لمعرفة فاعلية العلاج المعرفي المستند الى الوعي الكامل في علاج اضطراب الشدة ما بعد الصدمة أو ما يسمى أيضا في بعض أدبيات الطب اضطراب الشدة التالي للرض. تم تطبيق برنامج علاجي متضمن لتقنيات العلاج المعرفي وتقنية الوعي الكامل التي تحدث بها زيندل و سيجال على عينة من المرضى المراجعين لإدارة الخدمات الطبية التابعة لوزارة الداخلية السورية وتم اختيار نموذج حالة لتوضيح آلية تطبيق التقنيات ونتائج تطبيقها. أظهرت النتائج فعالية العلاج المعرفي بالوعي الكامل في علاج اضطرب الشدة التالي للرض حيث تراجعت أعراض الاضطراب وعاد المريض لحياته اليومية وعمله بعد أن كان قد اعتزلهما.Abstract: This study aimed to determine the effectiveness of mindfulness-based cognitive therapy in the treatment of post-traumatic stress disorder. A therapeutic program, including cognitive therapy techniques and mindfulness technique, (Zindel et Segal, 2006) was implemented on a sample of patients who visited the Department of Medical Services of the Syrian Ministry of the Interior. A case model was chosen to illustrate the mechanism for applying the techniques and obtained results. The Beck 21 depression scales and the RSCL-90 Mental Health Scale were used to assess the change in the patient's condition in two pre- and post-applications. The results showed, the effectiveness of cognitive therapy of Mindfulness in the treatment of post-traumatic stress disorder. Where the symptoms of the disorder decreased, and the patient resumed his daily life.
في علاج اضطراب الشدة التالي للصدمة
مقال
Keywords: عالج بالوعي الكامل؛ عالج المعرفي؛ اضطراب الشدة التالي للرض PTSD; Therapy of Mindfulness؛ Therapy cognitive؛ PTSD